Psychometric Evaluation of the Questionnaireа Diagnosing the Emotional Component of Essential Self-Regulation (ODES-2-E) - Kocharian, Igor (Psychological Counseling and Psychotherapy, 2025)
This article presents a psychometric evaluation of the questionnaire designed to assess the emotional component of Essential Self-Regulation" (ODES-2-E), designed to study the deep mechanisms of emotional functioning in personality. The theoretical foundation of the method is the concept of essential self-regulation, which is understood as a person’s ability to maintain authenticity, internal integrity, and meaningful coherence in response to external influences, while remaining in contact with their own values, needs, and tendency toward self-actualization. Thus, the method aims not only to assess the functional level of regulation but also to diagnose the emotional and existential core of personality. The instrument includes four scales: affect (emotional arousal, impulsivity), ambivalence (emotional contradiction), optimum (internal coherence, balance), and apathy (emotional detachment, exhaustion). Each scale is assessed within three life domains: general, professional, and family. The structure consists of six situational blocks, each presenting eight response options. Respondents choose 3–5 options that best reflect their emotional reaction, allowing the multidimensionality of emotional experience to be captured. Psychometric analysis indicates satisfactory reliability of the scales (Cronbach’s alpha ranging from 0.71 to 0.78), high item discrimination, and 75% agreement with the theoretical model (according to factor analysis). Construct validity is confirmed by statistically significant correlations with other psychological instruments: Hall’s Emotional Intelligence Test, Ryff’s Psychological Well-Being Scale, and Rabinovich’s Four-Modal Emotional Questionnaire. Scale standardization enables interpretation of results both in percentages and in raw scores using normative thresholds. Additionally, gender differences were analyzed: women scored higher on the ambivalence scale, while men scored higher on the apathy scale, suggesting possible differences in emotional engagement and regulation. The method is suitable for individual assessment, scientific research, psychotherapy, education, and training. It allows not only for diagnosing the state of emotional self-regulation but also for identifying personal resources, areas for development, and directions for personal growth.